Analisis Hukum Persetujuan Lingkungan terhadap Reklamasi Ilegal PT. Panca Anugrah Nusantara - Astuti, Alfina Sofi; Kadir, Kayla Nurhaliza; Hanifa, Zheylla Putri; Kamal, Ubaidillah (CV Insan Kreasi Media, 2025)
This study examines the legal violation aspects that occurred in the illegal reclamation project carried out by PT Panca Anugrah Nusantara (PT PAN) in the coastal area of Tanjung Pendam, Belitung. PT PAN was proven to have carried out reclamation activities without obtaining AMDAL, UKL-UPL documents, or valid environmental approvals in accordance with the provisions of Law Number 32 of 2009. The main focus of this study is to analyze the implementation of environmental approvals in reclamation projects and assess the legal consequences of the violations that occurred. This research was conducted through a normative legal approach with qualitative methods, reviewing legal regulations and relevant court decisions. These findings underline the importance of strengthening participatory mechanisms in the AMDAL preparation process and the need for strict law enforcement against violating corporations. The court decision imposing sanctions on PT PAN is an important precedent in enforcing criminal liability for legal entities. This study suggests the need for comprehensive reform in the licensing system, the implementation of technology-based supervision, and substantial increase in public participation in order to realize sustainable and environmentally fair reclamation.